2021
DOI: 10.1016/j.foodcont.2021.108085
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing chemical and biological risks in urban agriculture: A comprehensive framework for a food safety assessment of city region food systems

Abstract: Attention to urban agriculture (UA) has recently grown among practitioners, scientists, and the public, resulting in several initiatives worldwide. Despite the positive perception of modern UA and locally grown, fresh produce, the potential food safety risks connected to these practices may be underestimated, leading to regulatory gaps. Thus, there is a need for assessment tools to evaluate the food safety risks connected to specific UA initiatives, to assist practitioners in self-evaluation and control, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 135 publications
0
23
0
1
Order By: Relevance
“…While these additional risks are minimal for small-scale UA, the practice of commercial-scale UA using soil-base farming will bring the same risks as agro-industrial farms do on their surrounding environment. Buscaroli et al. (2021) identified three cases where plant protection products (PPP) used in UA may cause harm to its environment, these are, “ 1) disregard for precautionary limitations, 2) misuse of authorized active substances, and c) use of unauthorized substances.…”
Section: Different Contributions Of Urban Agriculture To Citymentioning
confidence: 99%
“…While these additional risks are minimal for small-scale UA, the practice of commercial-scale UA using soil-base farming will bring the same risks as agro-industrial farms do on their surrounding environment. Buscaroli et al. (2021) identified three cases where plant protection products (PPP) used in UA may cause harm to its environment, these are, “ 1) disregard for precautionary limitations, 2) misuse of authorized active substances, and c) use of unauthorized substances.…”
Section: Different Contributions Of Urban Agriculture To Citymentioning
confidence: 99%
“…2 Keamanan pangan dapat mempengaruhi perilaku konsumsi masyarakat, 3 seperti adanya pestisida dan pupuk yang digunakan petani merupakan salah satu penyebab kekhawatiran masyarakat dalam mengkonsumsi bahan makanan dari produk pertanian. 4 Logam berat dapat masuk ke tubuh manusia melalui 3 jalur yaitu penelanan, inhalasi dan kontak kulit, 5 konsumsi makanan merupakan jalur utama paparan logam berat dapat terakumulasi pada tubuh manusia. 6 Beberapa bahan makanan yang sering dikonsumsi masyarakat dan mengandung logam berat berdasarkan penelitian yang telah dilakukan antara lain makanan seafood 7 seperti Ikan 8 , udang 9 , dan bahan makanan dari tanaman pangan yang meliputi serealia (padi, beras, jagung, dll), buah dan sayuran.…”
Section: Pendahuluanunclassified
“…Also, a lot of studies are focusing on food safety and chemistry, such as untargeted food chemical safety assessment (Delaporte et al 2019 ), chemical safety of recycled food packaging (Geueke et al 2018 ), and chemical food safety hazards of sausages (Halagarda et al 2018 ). Furthermore, studies on food safety and agriculture include but are not limited to chemical and biological risks in urban agriculture (Buscaroli et al 2021 ), biosensors for sustainable agriculture and food safety (Griesche and Baeumner 2020 ), agricultural soil contamination, and the impact on food safety (Wang et al 2019b ). In addition, the Materials Science category was also on the top list, which indicated that materials are also important research directions in environment and food safety.…”
Section: A Scientometric Reviewmentioning
confidence: 99%